Temperature and pH influence the susceptibility of Salmonella Typhimurium to nisin combined with EDTA. (March 2016) - Prudêncio, Cláudia Vieira; Mantovani, Hilário Cuquetto; Cecon, Paulo Roberto; Prieto, Miguel; Vanetti, Maria Cristina Dantas
Abstract: Lantibiotics, such as nisin, generally act on Gram-positive bacteria, whereas Gram-negative bacteria exhibit natural resistance to the action of these bacteriocins. However, Gram-negative bacteria can become susceptible to the action of these antimicrobial peptides with the use of chelating agents, such as EDTA. The activity of bacteriocins can be influenced by several factors, such as environmental conditions and chemical composition of the medium. Moreover, the susceptibility of target microorganism can be altered, due to changes in cellular composition induced by environmental conditions. In this study, we examined the combined effect of variations in temperature and pH on the susceptibility of Salmonella Typhimurium to the action of nisin associated with EDTA. The reduction in the number of viable cells of Salmonella Typhimurium varied according to the temperature and pH, and major reduction in logarithmic cycles of viable cells occurred with a temperature increase. Under low temperature and low pH, a considerable reduction in the viability was also observed after prolonged exposure to bacteriocin, regardless of the presence of EDTA. According to results, temperature and pH conditions influence on the susceptibility of Salmonella Typhimurium to combination of nisin and EDTA and thus should be considered to establish optimal conditions for nisin use. Highlights: Temperature and pH influenced the action of nisin and EDTA on Salmonella Typhimurium. Nisin alone demonstrated activity inhibitory on Salmonella Typhimurium. Cells treated with nisin and EDTA showed an increase in viability.